The Increased Early Marriages Among Girl Children Between 14-17 years in Uganda : a case study of katimba village kiruhura district - Tusimire, Merab (Mukono : Uganda Christian University, 2010)
Discriptive Cataloguing Uganda Christian University BCDCM
Includes references and appendix
Keywords: early marriages among girl children